Adobe Photoshop lightroom 4 FAQs : 365 of your lightroom 4 questions answered - Sholik, Stan (John Wiley & Sons, 2012)
Get the answers to 365 of the most commonly asked questions about Lightroom Photographers who are getting acquainted with Photoshop Lightroom and all its advantages for managing large quantities of images will find this handy book an indispensable resource. Veteran photographer Stan Sholik answers 365 of the most frequently asked questions about the new Lightroom 4 in an informative, practical format, making it easy to find what you're looking for and put the information to use. Sample photos illustrate questions and answers, and a quick-reference guide provides easy access to must-ha.